Relationship Between Smoking and Ischemic Stroke: Meta Analysis - Sakinah Sakinah; Septyan Dwi Nugroho (Journal of Epidemiology and Public Health, 2022)
Background: Ischemic stroke is a non-communicable disease that has irreversible and modifiable risk factors. One of the risk factors that can be changed in preventing ischemic stroke is smoking behavior. The purpose of this study was to determine the relationship between smoking and the incidence of ischemic stroke from several previous studies. Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO model as follows. Population= Patients at Risk of Ischemic Stroke, Intervention= Smoking, Comparison= Not Smoking, and Outcome= Ischemic Stroke Incidence. The articles used in this study were obtained from several databases including PubMed and ScienceDirect. This article was collected within 1 month. The keywords to search for articles were as follows: Current AND Smoking OR Tobacco OR Cigarettes AND Hypertension AND "Ischemic Stroke" OR CVA (Cerebrovascular Accident). Results: Nine articles reviewed in this meta-analysis were from Lebanon, Mexico, Pakistan, Finland, Pakistan, United States of America, Saudi Arabia, Bangladesh, Iran. In this study, smokers had a 1.66 times risk of developing an ischemic stroke compared to nonsmokers and it was statistically significant (aOR= 1.66; 95%CI= 1.48 to 1.86; p< 0.001). People who smoked had a 1.66 times risk. experienced the incidence of isleemic stroke compared to non-smokers and was statistically significant (aOR= 1.66; 95%CI= 1.48 to 1.86; p< 0.001). Conclusion: Smoking has a relationship with the occurrence of ischemic stroke in at-risk patients. Keywords: smoking, hypertension, ischemic stroke. Correspondence: Septyan Dwi Nugroho. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: septyandwin@gmail.com. Mobile: 081804418933.